The Current State of Professional Competence Development of Future Primary School Teachers on the Basis of a Creative Approach - Xujayarova Nafisa Sultonmurodovna (International Journal on Integrated Education, 2022)
In the article, the theoretical rules for the improvement of the teacher's knowledge, skills and professional and personal qualities in the process of formation of general educational abilities of young students are explained